Potential valorization of granitic waste material as microproppant for induced unpropped microfractures in shale - Danso, D.K. (Elsevier B.V., 2021)
Billions of tons of quarried material are globally produced per annum, generating siliceous solid cutting and powder waste which are usually disposed of in landfill sites. Herein, two cheap and distinct granite quarry waste cuttings have been reduced into microproppant dimensions. They were characterized for potential application in hydraulic fracturing as an economic alternative to siliceous commercially available microproppants. The particle size distributions, morphology, particle density, the mineralogy, microscale mechanical hardness, and modulus of the produced microproppants were evaluated to confirm their potential application as microproppants. Also, the split core fracture conductivity of the produced microproppants was measured. Laser diffraction revealed particle size distribution with d50 of about 11 Î¼m suitable for common natural fracture widths. Morphological images showed low sphericity and roundness appropriate for channel fracturing proppant placement. A particle density of 2.6 and 2.9 g/cc was obtained for the produced microproppants. However, a review of most granite particle density indicated proximity to commonly used quartz-based microproppant. Their density and smaller sizes suggest good transport properties. Results of the mineralogy study showed high amounts of silica content with dominant crystal phases of albite, anorthite, and orthoclase which exhibited theoretical hardness between (5.2â7.2 GPa) and modulus between (77.8â98.0 GPa). Nanoindentation confirmed the micromechanical hardness and modulus determined by density functional theory. The hardness and modulus lie between class C Fly ash and Ottawa sand which have demonstrated good performance as microproppants. Hence granite microproppants have the potential to resist reservoir stresses. Granite microproppant pillars were able to improve the baseline permeability of a fractured shale core by a magnitude of ten. Granitic microproppants are cheaper sources of silica capable of maintaining microfracture width and preventing rapid production decline within unconventional shale reservoirs while contributing to the conservation of overly exploited natural sand deposits. Â© 2021 Elsevier B.V.